FORMULASI DAN KARAKTERISASI FITOSOM EKSTRAK TANAMAN BUNDUNG (Actinoscirpus grossus) SEBAGAI ANTIOKSIDAN - Noval; Febrianti, Dwi Rizki; Dwi Rizki; Melviani; Mayna; Salwa Nisrina; Akhmad Fadhil Samara (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2025)
Free radicals are the cause of cell damage and death. Free radical molecules are highly unstable and reactive, and can cause cell damage and metabolic disorders. Antioxidants are compounds that can reduce the negative impact of oxidants, enzymes, and metal-binding proteins. Bundung plant (Actinoscirpus grossus) contains secondary metabolite compounds namely flavonoids, tannins, saponins, phenolics, steroids, and terpenoids. Bundung showed moderate antioxidant activity with an IC50 value of 128 ppm. Flavonoids have high polarity, but are difficult to absorb due to their large size and poor solubility in lipids. Phytosomes can overcome the absorption barriers of natural active ingredients, by converting hydrophilic phytoconstituents into hydrophobic or lipid soluble components thereby increasing bioavailability through increased ability to cross cellular membranes and enter into blood circulation. The purpose of this study was to obtain the formulation and characterization of phytosomes of bundung plant extract as an antioxidant. The method uses maceration until a thick extract is obtained. Then, phytosomes of bundung extract were made by thin layer hydration method using rotary vaccum evaporator. The results showed that phytosomes of bundung extract in formula 4 were the most optimal, having a particle size value of 282.63 nm, a polydispersity index of 0.278 nm, a zeta potential of -5.89 nm, an absorption efficiency of 100%, and the best vesicle morphology was evenly distributed, had relatively the same size between one vesicle and another, and there was no aggregation between vesicles.